2020
DOI: 10.1055/s-0040-1715831
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Cardiopathy and Likely Pathogenic Patent Foramen Ovale in Embolic Stroke of Undetermined Source

Abstract: Background Atrial cardiopathy and likely pathogenic patent foramen ovale (PFO) are two potential embolic sources in patients with embolic stroke of undetermined source (ESUS). The relationship between these two mechanisms among ESUS patients remains unclear. Methods Atrial cardiopathy was defined as increased left atrial diameter index (> 23 mm/m2) or left atrial volume index (> 34 mL/m2), or PR prolongation (≥ 200 ms), or presence of supraventricular extrasystoles in the electrocardiograms per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…For instance, the presence of a pathogenic PFO is inversely related to the presence of non-stenotic ipsilateral carotid atherosclerosis in patients with ESUS 40. Additionally, the prevalence of a likely pathogenic PFO was found to be markedly lower in ESUS patients with atrial cardiopathy compared with those without atrial cardiopathy (3.3% v 23.7%; adjusted odds ratio 0.2, 0.02 to 0.6) 41…”
Section: Pathophysiology Of Pfo Associated Strokementioning
confidence: 95%
See 1 more Smart Citation
“…For instance, the presence of a pathogenic PFO is inversely related to the presence of non-stenotic ipsilateral carotid atherosclerosis in patients with ESUS 40. Additionally, the prevalence of a likely pathogenic PFO was found to be markedly lower in ESUS patients with atrial cardiopathy compared with those without atrial cardiopathy (3.3% v 23.7%; adjusted odds ratio 0.2, 0.02 to 0.6) 41…”
Section: Pathophysiology Of Pfo Associated Strokementioning
confidence: 95%
“…40 Additionally, the prevalence of a likely pathogenic PFO was found to be markedly lower in ESUS patients with atrial cardiopathy compared with those without atrial cardiopathy (3.3% v 23.7%; adjusted odds ratio 0.2, 0.02 to 0.6). 41 Paradoxical embolization refers to any passage of material between the right and left sides of the heart and can occur by way of a PFO, atrial septal defect, ventricular septal defect, or pulmonary arteriovenous fistula. This presumed mechanism of stroke associated with PFO is supported by several observations.…”
Section: Pathophysiology Of Pfo Associated Strokementioning
confidence: 99%
“…The patients were diagnosed with CS following multidisciplinary team assessment based on the classification of the trial of Org 10172 in acute stroke treatment (TOAST). [7] The major exclusion criteria were as follows: (1) more than one plausible cause of stroke, incomplete diagnostic assessments; (2) potential cardioembolic sources: heart failure, atrial fibrillation, moderate or higher valve regurgitation or stenosis, congenital heart disease except PFO; (3) malignant tumor, severe hepatic and renal insufficiency; (4) intrapulmonary shunt; (5) inadequate provocative maneuver. In the control group, MRI examinations were performed to confirm no cerebral ischemic lesion.…”
Section: Study Populationsmentioning
confidence: 99%
“…[3] However, recent research reported that LA dysfunction combined with PFO only accounted for 6.5% in CS patients. [4] LA dysfunction might be associated with overweight and hypertension in patients with PFO-attributable CS. [5] The size of LA could be easily determined in the clinic.…”
Section: Introductionmentioning
confidence: 97%
“…In this issue of Thrombosis and Haemostasis, Leventis et al 23 reported that the presence of atrial cardiopathy was inversely related to the presence of likely PFO in patients with ESUS. The prevalence of atrial cardiopathy was lower in patients with likely pathogenic PFO compared with patients with likely incidental PFO (31.2%) or without PFO, indicating that atrial cardiopathy and likely pathogenic PFO were two competing etiologies for ESUS.…”
mentioning
confidence: 99%